Semi‐Natural Habitats Buffer the Effects of Crop Diversification on Arthropod Pest Control Services in Agricultural Landscapes - Thomas Perrot; Léa Beaumelle; Eva Thomine; Yann Tricault; Nicolas Desneux; Matthias Albrecht; Péter Batáry; Felix Bianchi; Klaus Birkhofer; Aliette Bosem Baillod; Rebecca Chaplin‐Kramer; Anne‐Marie Cortesero; et al. (Ecology Letters, 2026)
Crop diversification is a promising strategy to strengthen pest control services in agricultural landscapes. Diversifying crops may limit pests through host crop dilution or by enhancing top‐down control by their enemies. However, crop diversification may also benefit generalist pests through higher resource continuity. Using a large‐scale dataset encompassing 742 landscapes across 13 countries, we assessed the impact of landscape‐scale crop diversity on the abundance of natural enemies, the potential for biological control, and insect pest abundance. Crop diversification did not increase the overall abundance of natural enemies or the potential for biological pest control. Instead, crop diversity primarily favoured the abundance of specialist natural enemies and pests in highly simplified landscapes, an effect that was reduced in landscapes with high proportions of semi‐natural habitats. Lastly, low proportions of host crops in the landscape were associated with higher abundances of natural enemies. Taken together, our results indicate that crop diversification is not a ‘one size fits all’ strategy to control agricultural pests, and that other landscape characteristics, such as high amounts of semi‐natural habitats, must be considered to enhance biological pest control services.

Analytical and clinical evaluation of a novel real-time PCR-based detection kit for Mpox virus - Till Bunse; Anne Ziel; Philipp Hagen; George Rigopoulos; Umit Yasar; Hakan Inan; Gurbet Köse; Ulrich Eigner; Rolf Kaiser; Nils Bardeck; Jasmin Köffer; Melissa Kolb; et al. (Medical Microbiology and Immunology, 2024)
Outbreaks of emerging diseases, like Mpox in 2022, pose unprecedented challenges to global healthcare systems. Although Mpox cases globally decreased since the end of 2022, numbers are still significant in the African Region, European Region, Region of the Americas, and Western Pacific Region. Rapid and efficient detection of infected individuals by precise screening assays is crucial for successful containment. In these assays, analytical and clinical performance must be assessed to ensure high quality. However, clinical studies evaluating Mpox virus (MPXV) detection kits using patient-derived samples are scarce. This study evaluated the analytical and clinical performance of a new diagnostic MPXV real-time PCR detection kit (Sansure Monkeypox Virus Nucleic Acid Diagnostic Kit) using patient-derived samples collected in Germany during the MPXV clade IIb outbreak in 2022. Our experimental approach determined the Limit of Detection (LoD) to less than 200 cp/mL using whole blood samples and samples derived from vesicles or pustules. Furthermore, we tested potentially inhibiting substances and pathogens with homologous nucleic acid sequences or similar clinical presentation and detected no cross-reactivity or interference. Following this, the assay was compared to a CE-marked test in a clinical performance study and achieved a diagnostic sensitivity of 100.00% and diagnostic specificity of 96.97%. In summary, the investigated real-time PCR assay demonstrates high analytical performance and concurs with the competitor device with high specificity and sensitivity.

Museomics help resolving the phylogeny of snowfinches (Aves, Passeridae, Montifringilla and allies) - Safiqul Islam; Claire Peart; Christian Kehlmaier; Yue-Hua Sun; Fumin Lei; Andreas Dahl; Sylvia Klemroth; Dimitra Alexopoulou; Maria del Mar Delgado; Paola Laiolo; Juan Carlos Illera; Sebastian Dirren; et al. (Molecular Phylogenetics and Evolution, 2024)

Predicting plant–pollinator interactions: concepts, methods, and challenges - Guadalupe Peralta; Paul J. CaraDonna; Demetra Rakosy; Jochen Fründ; María P. Pascual Tudanca; Carsten F. Dormann; Laura A. Burkle; Christopher N. Kaiser-Bunbury; Tiffany M. Knight; Julian Resasco; Rachael Winfree; Nico Blüthgen; et al. (Trends in Ecology & Evolution, 2024)

Seeing through the static: the temporal dimension of plant–animal mutualistic interactions - Paul J. CaraDonna; Laura A. Burkle; Benjamin Schwarz; Julian Resasco; Tiffany M. Knight; Gita Benadi; Nico Blüthgen; Carsten F. Dormann; Qiang Fang; Jochen Fründ; Benoit Gauzens; Christopher N. Kaiser‐Bunbury; et al. (Ecology Letters, 2021)
Most studies of plant–animal mutualistic networks have come from a temporally static perspective. This approach has revealed general patterns in network structure, but limits our ability to understand the ecological and evolutionary processes that shape these networks and to predict the consequences of natural and human‐driven disturbance on species interactions. We review the growing literature on temporal dynamics of plant–animal mutualistic networks including pollination, seed dispersal and ant defence mutualisms. We then discuss potential mechanisms underlying such variation in interactions, ranging from behavioural and physiological processes at the finest temporal scales to ecological and evolutionary processes at the broadest. We find that at the finest temporal scales (days, weeks, months) mutualistic interactions are highly dynamic, with considerable variation in network structure. At intermediate scales (years, decades), networks still exhibit high levels of temporal variation, but such variation appears to influence network properties only weakly. At the broadest temporal scales (many decades, centuries and beyond), continued shifts in interactions appear to reshape network structure, leading to dramatic community changes, including loss of species and function. Our review highlights the importance of considering the temporal dimension for understanding the ecology and evolution of complex webs of mutualistic interactions.

Significance of Beta-Band Oscillations in Autism Spectrum Disorders During Motor Response Inhibition Tasks: A MEG Study - Vera Moliadze; Alla Brodski-Guerniero; Magdalena Schuetz; Julia Siemann; Ekaterina Lyzhko; Sabine Schlitt; Janina Kitzerow; Anne Langer; Jochen Kaiser; Marcus J. Naumer; Michael Wibral; Jason Chan; et al. (Brain Topography, 2020)
In Autism Spectrum Disorders (ASD), impaired response inhibition and lack of adaptation are hypothesized to underlie core ASD symptoms, such as social communication and repetitive, stereotyped behavior. Thus, the aim of the present study was to compare neural correlates of inhibition, post-error adaptation, and reaction time variability in ASD and neuro-typical control (NTC) participants by investigating possible differences in error-related changes of oscillatory MEG activity. Twelve male NTC (mean age 20.3 ± 3.7) and fourteen male patients with ASD (mean age 17.8 ± 2.9) were included in the analysis. Subjects with ASD showed increased error-related reaction time variability. MEG analysis revealed decreased beta power in the ASD group in comparison to the NTC group over the centro-parietal channels in both, the pre-stimulus and post-response interval. In the ASD group, mean centro-parietal beta power negatively correlated with dimensional autism symptoms. In both groups, false alarms were followed by an early increase in temporo-frontal theta to alpha power; and by a later decrease in alpha to beta power at central and posterior sensors. Single trial correlations were additionally studied in the ASD group, who showed a positive correlation of pre-stimulus beta power with post-response theta, alpha, and beta power, particularly after hit trials. On a broader scale, the results deliver important insights into top-down control deficits that may relate to core symptoms observed in ASD.

The interplay of landscape composition and configuration: new pathways to manage functional biodiversity and agroecosystem services across Europe - Emily A. Martin; Matteo Dainese; Yann Clough; András Báldi; Riccardo Bommarco; Vesna Gagic; Michael P.D. Garratt; Andrea Holzschuh; David Kleijn; Anikó Kovács‐Hostyánszki; Lorenzo Marini; Simon G. Potts; et al. (Ecology Letters, 2019)
Managing agricultural landscapes to support biodiversity and ecosystem services is a key aim of a sustainable agriculture. However, how the spatial arrangement of crop fields and other habitats in landscapes impacts arthropods and their functions is poorly known. Synthesising data from 49 studies (1515 landscapes) across Europe, we examined effects of landscape composition (% habitats) and configuration (edge density) on arthropods in fields and their margins, pest control, pollination and yields. Configuration effects interacted with the proportions of crop and non‐crop habitats, and species’ dietary, dispersal and overwintering traits led to contrasting responses to landscape variables. Overall, however, in landscapes with high edge density, 70% of pollinator and 44% of natural enemy species reached highest abundances and pollination and pest control improved 1.7‐ and 1.4‐fold respectively. Arable‐dominated landscapes with high edge densities achieved high yields. This suggests that enhancing edge density in European agroecosystems can promote functional biodiversity and yield‐enhancing ecosystem services.

The potential for indirect effects between co‐flowering plants via shared pollinators depends on resource abundance, accessibility and relatedness - Luísa Gigante Carvalheiro; Jacobus Christiaan Biesmeijer; Gita Benadi; Jochen Fründ; Martina Stang; Ignasi Bartomeus; Christopher N. Kaiser‐Bunbury; Mathilde Baude; Sofia I. F. Gomes; Vincent Merckx; Katherine C. R. Baldock; Andrew T. D. Bennett; et al. (Ecology Letters, 2014)
Co‐flowering plant species commonly share flower visitors, and thus have the potential to influence each other's pollination. In this study we analysed 750 quantitative plant–pollinator networks from 28 studies representing diverse biomes worldwide. We show that the potential for one plant species to influence another indirectly via shared pollinators was greater for plants whose resources were more abundant (higher floral unit number and nectar sugar content) and more accessible. The potential indirect influence was also stronger between phylogenetically closer plant species and was independent of plant geographic origin (native vs. non‐native). The positive effect of nectar sugar content and phylogenetic proximity was much more accentuated for bees than for other groups. Consequently, the impact of these factors depends on the pollination mode of plants, e.g. bee or fly pollinated. Our findings may help predict which plant species have the greatest importance in the functioning of plant–pollination networks.

Sensory modality of smoking cues modulates neural cue reactivity - Yavor Yalachkov; Jochen Kaiser; Andreas Görres; Arne Seehaus; Marcus J. Naumer (Psychopharmacology, 2013)

Behavioural and electrophysiological effects of visual paired associate context manipulations during encoding and recognition in younger adults, older adults and older cognitively declined adults - Michael J. Hogan; Joanne P. M. Kenney; Richard A. P. Roche; Michael A. Keane; Jennifer L. Moore; Jochen Kaiser; Robert Lai; Neil Upton (Experimental Brain Research, 2012)

Investigating human audio-visual object perception with a combination of hypothesis-generating and hypothesis-testing fMRI analysis tools - Marcus J. Naumer; Jasper J. F. van den Bosch; Michael Wibral; Axel Kohler; Wolf Singer; Jochen Kaiser; Vincent van de Ven; Lars Muckli (Experimental Brain Research, 2011)

Electroencephalographic coherence, aging, and memory: distinct responses to background context and stimulus repetition in younger, older, and older declined groups - Michael Hogan; Peter Collins; Michael Keane; Liam Kilmartin; Jochen Kaiser; Joanne Kenney; Robert Lai; Neil Upton (Experimental Brain Research, 2011)